PROBLEMATIKA PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN PADA GURU KELAS DI SDN WONOKERSO 01 KABUPATEN MALANG - Febyanto, Chandy (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2016)
Professional teachers should be able to make designinstructions learning. The purpose of this study was to describethe qualitative information about the experience and capabilitiesof teachers towards the development of the design instructionsand implementation learning. The approach in this study i.e. thequalitative approach with descriptive research method. Theresults showed that the participants still had a less professionalexperience in designing and developing an design instructionss where there is the fact that the participants copy the designinstructions from the internet or from friends. Participants arealso still lacking in the ability carry out teaching in accordancewith design instructions learning with reason of administrativetasks that must be done at the same time and not able tomanage time learning. In addition there is also the fact of lack ofunderstanding of the participants for the right election ofmethod and media becomes a factor. The role of Governmentis highly expected in the overcome this situation through theexistence of training and workshop that on an ongoing basiswith involving professional organizations and working groups ofteachers so that teachers can exchange knowledge andexperience.